A framework for dependability evaluation of industrial processes - Daniel Macedo (2013)
There is a growing need to develop new tools to help end users in tasks related to the design, monitoring, maintenance and commissioning of industrial processes. The complexity of the industrial environment requires that these tools have flexible features in order to provide valuable data at the early planning and design phases. Furthermore, it is known that industrial processes have stringent requirements for dependability (reliability and availability), since failures can cause economic losses, environmental damages and danger to people. The lack of tools that enable the evaluation of faults in industrial processes could mitigate these problems. In this work we present a framework which is able to estimate the reliability and availability of industrial processes that can be modeled as a graph. The framework transforms the graph structure into a Fault Tree model in order to analyze their dependability. In order to validate the proposal we conduct a dependability study of an industrial process. © 2013 IEEE.